Scientific and strategic foresighting: The trajectory of sustainable development (on the example of Ukraine's energy security) - Yurii Kharazishvili; Yuriy Bilan; Oleksandr Sukhodolia; Olena Grishnova; Halyna Mishchuk (Sustainable Futures)
The emergence of the concept of sustainable development of society has prompted the search for national approaches to its management. The application of energy potential by individual countries as a tool of political influence requires a review of the approaches to analyzing the state of affairs in the field of energy security and scientific justification of strategic scenarios for maintaining the trajectory of sustainable development. The goal of the article is the further development of the model for analyzing a specific area of management in the security dimension and the methods of strategizing the development of such an area – scientific and strategic foresight for the development of strategic scenarios for post-war recovery using the example of Ukraine's energy security. To achieve the research goal, the concept of sustainable development in the security dimension was used, which includes the methodology for identification and strategizing based on the new principle “the trajectory towards a future determines the future” through solving the inverse problem of decomposing integral indices using adaptive regulation methods from control theory. The methods of integral evaluation, stochastic methods for determining the boundaries of safe existence (applied systems theory, t-test methods, cluster analysis), determination of dynamic weighting coefficients using principal component methods and sliding matrices, decomposition of integral indices, and denormalization of indicators in natural units of measurement are also applied. A model of energy security has been developed, which includes seven components and 47 indicators, including shadow indicators. The analysis concept involves first studying each individual component within a unified whole, followed by analyzing energy security as a whole – an identification stage for the current level of security. Subsequently, the sustainable development trajectories are built towards the defined goals, and the whole is decomposed into components that ensure the achievement of the set goals – strategizing. The elements of scientific novelty in scientific and strategic foresighting technology are formulated, which operate in the following modes: structural evolution, projected structural transformation – rapid structural transformation, and balanced sustainable development. The mechanism for regulating the speed of structural restructuring through the regulation of constraints has been identified. Within these modes, models for the development of Ukraine's energy sector in the post-war period have been developed and studied: evolutionary development, green transition, and energy supply resilience for consumers.